Die Akzeptanzanalysen: staatliche Familienleistungen aus Sicht der Bevölkerung - Wilhelm Haumann (Vierteljahrshefte zur Wirtschaftsforschung, 2014)
Im Rahmen der Gesamtevaluation der familienbezogenen Leistungen untersuchte das Allensbacher Institut mit zwei Akzeptanzanalysen 2010 und 2011 die Bekanntheit und die Bewertung von 16 staatlichen Leistungen zur Familienförderung sowie die Muster der Inanspruchnahme. Die qualitativen und quantitativen Untersuchungen zeigen eine breite Nutzung der Leistungen. Etwa die Hälfte der erwachsenen Bevölkerung berichtet über die Nutzung von Leistungen durch Mitglieder ihres Haushalts. Die Mehrzahl der aktuellen Nutzer bewerten die meisten der untersuchten Leistungen als große Hilfe für ihre Familie. Ausbaubedarf für die Förderung wird besonders für Alleinerziehende, geringverdienende Eltern und Arbeitslosen oder sozial Schwachen mit Kindern gesehen. Zudem wünschen sich viele Eltern zusätzliche Betreuungsmöglichkeiten für Kinder unter drei Jahren sowie für jüngere Schulkinder. Eine vertiefende Untersuchung der Kinderbetreuung und -förderung zeigt die große Bedeutung der Betreuungsangebote für die Förderung von Kindern wie auch für die Erwerbsmöglichkeiten von Müttern. Im Hinblick auf die Alterssicherung von Familien werden unterschiedliche Kenntnisse, Einstellungen und Absicherungsstrategien erkennbar. Mütter verlassen sich für ihre Alterssicherung häufig auf die Vorsorge ihres Partners. – – Within the framework of the overall evaluation of family-related benefits, the Allensbach Institute completed two acceptance analyses in 2010 and 2011 on the population's familiarity with and assessments of 16 different state benefits intended to support families, along with benefit claiming patterns. The qualitative and quantitative parts of the study indicate that family benefits are claimed by broad swaths of the population. About half of the adult population reports that someone in their household makes use of family benefits. The majority of persons currently making use of family benefits say that most of the benefits studied are of great help to their families. The population perceives a need to expand benefits particularly for single parents, low-income families and for unemployed or socially disadvantaged persons with children. In addition, many parents express a desire for additional day care optionsfor children under age 3 and for younger school children. A more detailed investigation on the issue of child care services and developmental programs shows the great significance of these services when it comes to both promoting the well-being of children and enabling mothers to work. Regarding their plans to provide for their old age, the studies reveal different levels of knowledge among German families, along with a diverse range of attitudes and retirement saving strategies. Mothers often depend on their partner's pension and retirement income for security in their old age.
Keywords: H31; J13; J32; H55; 330; Family economics; fiscal policies; family support programs; subsidy; tax benefit; tax system; childcare; child support; retirement pension